A Study of Childfree Understanding as a Form of Birrul Walidain Among Students of State Senior High School 1 Patean in 2025 - Asih Budiharti; Abdul Majid; Maurisa Zinira; Abdurrohman Al Asy'ari; Salis Irvan Fuadi; Nur Wahyuni Anisa (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2026)
The childfree phenomenon, widely discussed on social media, has become a contemporary social issue influencing adolescents' perspectives on family and marriage. For high school students at SMA N 1 Patean, this issue intersects with individual freedom and the development of the birrul walidain character. This study aims to analyze students' understanding of childfree and its role in developing devotion to parents. The main focus examines how students perceive childfree and how Islamic Religious Education (PAI) and the school environment contribute to instilling birrul walidain values amidst this issue. Using a qualitative case study design, data were collected through in-depth interviews with students and PAI teachers, observations, and supporting documentation. The data were analyzed descriptively to illustrate patterns of student understanding and their relationship to character development. Results showed that most students learned about childfree through social media, interpreting it partially as personal freedom. Religious education in schools plays a crucial role in clarifying students' perspectives by emphasizing family values, moral responsibility, and devotion to parents. These findings highlight that strengthening faith-based character education is necessary to foster critical thinking while maintaining filial piety. In conclusion, students' understanding of childfree can serve as a reflective tool in developing birrul walidain character when guided through appropriate educational approaches. Consequently, schools need to integrate contemporary social issues into PAI learning to strengthen moral character. Future research is recommended to expand the scope and methodology to obtain a broader picture of the relationship between social media trends and adolescent character development.